Strengthening role of health sectors in gender based violence - Dash, Rozaleen; Singh, M. Meghachandra (International Journal Of Community Medicine And Public Health, 2017)
Gender based violence (GBV) is a global public health concern that has only relatively recently received significant research and policy attention. GBV is a common reality in the lives of women and girls in many parts of the world, developing and industrialised countries alike. It has been recognized as a violation of basic human rights of women and of their exercise of fundamental freedom. GBV against women has now been acknowledged as a major public health issue. It affects people of all socioeconomic backgrounds and education levels. The management of GBV essentially requires combined effort of health care services, social welfare and law enforcement. The response of health services to GBV is an international priority. Although efforts have been made in this direction, the attended cases represent just the tip of the iceberg, as majority of the cases are not reported due to social pressures from family members or social stigma of defamation. Real change in these cases can only be brought about by educating healthcare providers and better law enforcement. To conclude it is therefore necessary that every member of society and organizations are duty bound to ensure that every woman lives a violence free life.